APLIKASI BIANG PGPR (PLANT GROWTH PROMOTING RHIZOBACTERIA) DARI AKAR BAMBU TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PARE (Momordica charantia L): APPLICATION OF PGPR (PLANT GROWTH PROMOTING RHIZOBACTERIA) FROM BAMBOO ROOTS THE GROWTH AND YIELD OF PARIAH PLANTS (Momordica charantia L) - Roy Naldo Doane; Mihwan Sataral; Dwi Maharia (Fakultas Pertanian Universitas Tompotika Luwuk, 2022)
Paria (Momordica charantia L) is one of the plants from the Cucurbitaceae tribe or the pumpkin tribe, including lowland vegetables, and is classified as a herbaceous plant aged one year or more, growing creeping and climbing. PGPR (Plant Growth Promoting Rhizobacteria) bamboo roots are bacteria that live around the roots of bamboo plants. The purpose of this study was to determine the effect of PGPR from bamboo roots and the right concentration on the growth and yield of pariah plants. This research was conducted in Kelapa Lima village, South Banggai District, Banggai Laut Regency from August 2021 to November 2021. This study used a one-factor randomized block design (RBD) method. This study consisted of 5 levels of treatment, namely: P0 = control, P1 = concentration of 12.5 ml/liter of water, P2 = concentration of 15 ml/liter of water, P3 = concentration of 17.5 ml/liter of water and P4 = concentration of 20 ml / liter of water. Each treatment was repeated five times so that there were twenty-five experimental units. The results showed that the application of PGPR from bamboo roots had a significant effect on plant height at 5 WAP, 7 WAP, and 8 WAP, significantly affected the number of leaves at 3 WAP, 5 WAP, 7 WAP, and 8 WAP, very significant effect on fruit weight, fruit length, and fruit diameter and had no significant effect on the number of pariah fruit.